Penerapan Media Pembelajaran Audio Visual Untuk Meningkatkan Kemampuan Siswa Dalam Membaca Al – Qur’an Dan Hadis Pada Mata Pelajaran Qurdis - Fauziah, Hapsah; Alamsyah, Fikri Firdaus (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
This research discusses the application of audio visual learning media and its implications for improving students' abilities in reading the Al-Qur'an and Hadith in Qurdis subjects in Class VII-2 MTs. Al-Musaddadiyah Garut. The ability to read the Al-Qur'an is an individual's ability to read the Al-Qur'an properly and correctly in accordance with applicable rules. However, in reality the ability to read the Al-Qur'an of students in class VII-2 MTs. Al Musaddadiyah Garut is still relatively low, this is proven by the results of pre-research observations. Only around 44% of the 31 students demonstrated their ability to read the Koran effectively, this was due to several factors, including family factors where both parents were busy working and only lived with their grandmother. So there is a lack of supervision and attention, in addition to environmental factors that are less supportive, where after being asked this child often plays with his cellphone so he forgets time and disturbs his time for reciting the Koran, as a result he is reciting the Koran at home alone without assistance. After a home visit, the child turned out to be a victim of his parents' divorce. Meanwhile, his mother's whereabouts are unknown, so stimulus is needed, one of which is using learning media, namely audio-visual media. The aim of this research is to describe the significance of students' ability to read the Al-Qur'an and Hadith in Class VII-2 MTs. Al–Musaddadiyah Garut, describes the application of audio visual learning media to students' ability to read the Koran and Hadith in Class VII-2 MTs. Al–Musaddadiyah Garut, described the increase in students' ability to read the Al-Qur'an and Hadith in Class VII-2 MTs. Al-Musaddadiyah Garut Using Audio Visual Media and Its Implications. The method used is Classroom Action Research (PTK). Data collection techniques include observation, questionnaires, Al-Qur'an reading tests, interviews and documentation. The data analysis technique in PTK only uses simple statistical formulas to find the average value and percentage of students' Al-Qur'an reading ability assessments. Based on the results of classroom action research conducted in two cycles, there was a quite drastic increase in students' ability to read the Al-Qur'an in cycle I to 71%, then experienced another increase in cycle II to 82%. It can be understood that there is an increase in the ability to read the Al-Qur'an from the results of the Al-Qur'an reading test with a significance of 27% from pre-cycle to cycle I and 11% from cycle I to cycle II. So, overall there was an increase in students' ability to read the Al-Qur'an with a significance of 38% from pre-cycle to cycle II.  Keywords: Islamic Religious Education, Ability to Read the Qur'an and Hadits, Audio Visual Media